Investigations of Flow and Species Transport in Packed Beds by Lattice Boltzmann Simulations - Zeiser, Thomas (High Performance Computing in Science and Engineering ' 06: Transactions of the High Performance Computing Center, Stuttgart (HLRS) 2006, 2007)
This report summarizes selected results of investigations of the flow and species transport in packed beds. First of all, the difficulty of segmenting image data with respect to the correct choice of the threshold value and thus the resulting porosity is discussed. Then, the accuracy of lattice Boltzmann flow simulations is compared with CFX-5 simulations. The 3-D flow data is furthermore used to show how the pressure drop is made up by shear forces and dissipation owing to elongation and deformation. For the species transport, a random walk particle tracking algorithm is used to complement the lattice Boltzmann method thus allowing a wide range of Peclet numbers. In the last part, preliminary performance results of a new 1-D list based lattice Boltzmann implementation ("sparse lattice") are summarized which soon will replace the currently used full array based code. It is shown that outstanding performance on vector as well as cache based parallel computers can be achieved with this 1-D list based "sparse lattice" code, too. Despite sophisticated optimizations for cache based microprocessors, the sustained application performance of a single NEC SX-8 CPU is about 10-20 times higher than that of any commodity CPU. For parallel calculations, this gap even grows further.
UnivIS-Import:2015-04-20:Pub.2007.zwiss.rrze.zensys.invest